Japan – Republic of Korea: A New Rapprochement? - D. V. Streltsov (Сравнительная политика, 2024)
Since the end of the Cold War the relations between South Korea and Japan have developed in a non-linear manner. The most recent period is no exception. Following the cooling, witnessed since 2017, there has been a warming between the two countries, largely due to a qualitative change in Seoul’s policy towards Tokyo when Yoon Suk Yeol’s administration came to power in May 2022. The advances in the DPRK’s nuclear missile program as well as China’s assertive military policy began to push South Korea towards closer security cooperation with Japan. The internal political dynamics in the Republic of Korea, including the growth of anti-Chinese sentiment, the disappointment with the ‘soft’ policy towards the DPRK pursued by the previous ‘progressive’ administration, as well as the personal ambitions of the new president contributed to the warming of relations with Japan. Washington’s activity also played a role, as it tried to ‘reconcile’ its allies and intensify their military and political cooperation within the US – Japan – South Korea triangle. Analyzing the series of summits held in 2023 between the leaders of the Republic of Korea and Japan, the author comes to conclusion that the two states put their historical grievances aside and gave priority to establishing close bilateral and trilateral (including the United States) cooperation, primarily in the fields of international politics and security. For the first time since the end of the Cold War, Japan and South Korea began to actively strengthen their military and political ties, not only on the anti-North Korean, but also on the anti-Chinese and the anti-Russian basis.